2019
DOI: 10.1016/j.euroneuro.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting injectable antipsychotics (LAIs) for maintenance treatment of bipolar and schizoaffective disorders: A systematic review

Abstract: Long-Acting Injectable Antipsychotics (LAIs) are used to overcome non-compliance in psychoses, mainly schizophrenia spectrum disorders. We aimed to summarize available evidence of studies comparing the efficacy of LAIs to placebo or oral medications for Bipolar Disorder JID: NEUPSY [m6+; February 12, 2019;11:45 ] Long-acting injectable antipsychotic treatment; Risperidone long-acting; Paliperidone palmitate long-acting injectable; Aripiprazole monohydrate long-acting injectable (BD) and/or Schizoaffective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 54 publications
2
45
0
1
Order By: Relevance
“…In addition, PP1M seems to have some efficacy in the management of psychotic or non-psychotic BD in our study, which is consistent with previously demonstrated efficacy of paliperidone ER and PP1M in patients with current manic or mixed episodes, schizoaffective disorders (15), or psychotic BD (21). However, depressive episode was detected in three cases, suggesting that PP1M may be less effective in the prevention of depression, which is in line with the idea that depot neuroleptics showed better efficacy in preventing mania than depression (27). Combined with the fact that manic symptoms are more associated with non-compliance than depressive symptoms (28), BD with a predominance of manic symptoms may be more suitable to use PP1M.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, PP1M seems to have some efficacy in the management of psychotic or non-psychotic BD in our study, which is consistent with previously demonstrated efficacy of paliperidone ER and PP1M in patients with current manic or mixed episodes, schizoaffective disorders (15), or psychotic BD (21). However, depressive episode was detected in three cases, suggesting that PP1M may be less effective in the prevention of depression, which is in line with the idea that depot neuroleptics showed better efficacy in preventing mania than depression (27). Combined with the fact that manic symptoms are more associated with non-compliance than depressive symptoms (28), BD with a predominance of manic symptoms may be more suitable to use PP1M.…”
Section: Discussionsupporting
confidence: 92%
“…In this line, LAIs ought to be considered and offered as maintenance treatment in patients with poor adherence (82). Aripiprazole monohydrate once-monthly LAI monotherapy has shown to delay time to recurrence of manic episodes without inducing depressive episodes (83).…”
Section: The Management Of a Manic Episodementioning
confidence: 99%
“…Aripiprazole monohydrate once-monthly LAI monotherapy has shown to delay time to recurrence of manic episodes without inducing depressive episodes (83). Risperidone LAI monotherapy (84) or adjunctive therapy (85) was found to be effective in protecting from manic, but not depressive recurrences (82). The studies regarding the use of paliperidone palmitate LAI in the treatment of BD are limited to case-reports (86,87).…”
Section: The Management Of a Manic Episodementioning
confidence: 99%
See 1 more Smart Citation
“…Hasta la fecha, no se ha publicado ningún ECA en pacientes con trastorno bipolar 27 , pero sí en pacientes con esquizofrenia. En el tratamiento agudo de la esquizofrenia, el OP (210 mg/2 sem, 300 mg/2 sem y 405 mg/4 sem) demostró ser tan eficaz como su homólogo oral (olanzapina 2,5-15 mg/d) y superior a placebo en remisión clínica y tasas de discontinuación 28 .…”
Section: Olanzapina Pamoatounclassified